Hubungan Higiene Sanitasi dengan Kontaminasi Bakteri Escherichia Coli pada Minuman Es Teh: (Studi di Kelurahan Latsari, Kecamatan Tuban) - Defrika Maulidia Salma; H. Miftahul Munir (Lembaga Pengembangan Kinerja Dosen, 2026)
Iced tea is a popular beverage due to its accessibility and affordability. However, poor hygiene and sanitation practices can lead to contamination by pathogenic microorganisms such as Escherichia coli, which can potentially cause foodborne diseases. Sanitation practices, including cleanliness of vendors, equipment, and processing facilities, play a crucial role in ensuring the safety of beverages consumed by the public. The research method used was a quantitative study with an observational analytical design using a cross-sectional approach. Total sampling was used, with 21 iced tea vendors as the sample. The independent variable in this study was sanitation hygiene, while the dependent variable was Escherichia coli bacterial contamination in iced tea. The results of the study conducted on 21 respondents showed that iced tea drink sellers with qualified sanitation hygiene practices with a total of 10 respondents, 8 samples of iced tea drinks were negative for Escherichia Coli and 2 samples of iced tea drinks were positive for Escherichia Coli. While iced tea drink sellers who did not meet the requirements for sanitation hygiene practices were 11 respondents, with 11 samples of iced tea drinks positive for Escherichia Coli bacteria. After being analyzed using the IBM SPSS Statistics 24 Application, a p-value of 0.000 (<0.05) was obtained, so H1 was accepted, it was concluded that there was a relationship between sanitation hygiene and Escherichia Coli bacterial contamination of iced tea drinks. Based on the description above it can be concluded that the low sanitation hygiene practices carried out by iced tea drink sellers can increase the risk of Escherichia Coli bacteria contamination in drinks and will affect the quality and safety of drinks that will be consumed by the public.